Comparison of thoracic kyphosis in two groups of elite Greco-Roman and freestyle wrestlers and a group of non-athletic participants. Issue 3 (5th July 2007) - Rajabi, R; Doherty, P; Goodarzi, M; Hemayattalab, R
Abstract : Background: Freestyle and Greco-Roman are two types of wrestling that place the spine of athletes in different positions. Theoretically, it can be argued that this can lead to adverse effects on the spine and might be an important factor associated with changes in the degree of kyphosis. Objectives: The aim of this study was to investigate whether the extent of thoracic kyphosis differs in two groups of elite wrestlers and a group of non-athletic participants. Methods: Sixty elite Iranian male wrestlers including 30 freestyle (mean (SD) age 23.5 (2.8) years, height 176 (7.1) cm and weight 77.8 (16.1) kg) and 30 Greco-Roman (age 23.9 (2.9) years, height 176 (4) cm and weight 80.1 (11.1) kg) wrestlers and 30 male non-athletes (age 23.3 (2.1) years, height 175 (8) cm and weight 75.2 (6.7) kg) were recruited. All wrestlers competed at international level with the Iranian national team or Iranian student national team. Each selected wrestler had to meet a minimum criterion of 5 years' wrestling. The degree of kyphosis was measured using a modified electrogoniometer. Results: Mean (SD) kyphosis was 30° (3.8), 24.3° (3.7) and 27.4° (3.2) for the freestyle, Greco-Roman style and non-athlete groups, respectively. A significant difference was found in mean kyphosis between all groups (p<0.05) with freestyle being the highest and Greco-Roman the lowest. Conclusions: The degree of kyphosis was highest in freestyle wrestling, followed by non-athletes and then Greco-Roman wrestlers. The extent of kyphosis was not influenced by years of training or age of starting wrestling.